RECONFIGURABLE POWER AMPLIFIER WITH TUNABLE INTERSTAGE MATCHING NETWORK USING GaAs MMIC AND SURFACE-MOUNT TECHNOLOGY - Gani, Regina Gani (2010)
As the demand of reconfigurable devices increases, the possibility of exploiting the interstage matching network in a two-stage amplifier to provide center frequency tuning capability is explored. While placement of tuning elements at the input and/or output matching network has some disadvantages, placement of tuning elements in the interstage absorbs the lossy components characteristics into useful attributes. The circuit design methodology includes graphical method to determine the bandpass topology that achieves high Q-contour on the Smith chart thus result in narrow bandwidth. T-section and π-section topologies are used to match reactive terminations provided by the first and second amplifier stages. The design methodology also includes utilization of interstage mismatch loss that decreases as increasing frequency to compensate for amplifier gain roll-off and equalize the gain at different tuning states. In prototype realization, three design configurations are discussed in this thesis: 1) a discrete design for operation between 0.1 – 0.9 GHz with the total layout area of 7.5 mm x 12.5 mm, 2) a partial monolithic design (Quasi-MMIC) for operation between 0.9 – 2.4 GHz that is 25 times smaller layout area compared to the discrete design, and 3) a conceptual design of integrated monolithic reconfigurable PA for operation between 0.9 – 2.4 GHz that is 130 times smaller layout area compared to the discrete design. One variant of the fabricated reconfigurable PA offers advantage of 4-states center frequency tuning from 1.37 GHz to 1.95 GHz with gain of 21.5 dB (+ 0.7 dB). The feasibility of interstage matching network as tuning elements in reconfigurable power amplifier has been explored. The input and output matching networks are fixed while the interstage impedances are varied using electronic switching (discrete SP4T and GaAs FET switches). The discrete design is suited for the operation at low frequency (fo < 1GHz), while monolithic implementation of the tunable interstage matching network is required for higher frequency operation due to size limitation and parasitic effects. The reconfigurable PA using MMIC tuner was designed at higher frequency to possibly cover GSM, CDMA, Bluetooth, and WiMAX frequency (0.9 – 2.4 GHz).